PANDANGAN PENGHULU DI KABUPATEN AGAM DAN TINJAUAN MAQASHID SYARIAH TENTANG PENGGUNAAN TEKNOLOGI INFORMASI DALAM TAUKIL WALI NIKAH - reviko, Reviko (Ahkam: Jurnal Hukum Islam, 2023)
Taukil wali nikah through information technology means the delegation of power and authority by the marriage guardian to another in the marriage contract by using information technology. This research aims to describe the implementation of taukil wali nikah through information technology and the opinion of penghulu in Agam Regency from the perspective of maqashid sharia with focus on two questions; first, how is the implementation of taukil wali nikah through information technology in Agam Regency, second, how is taukil wali nikah through information technology according to the opinion of the penghulu in Agam Regency from the perspective of maqashid syariah. This research use desciptive qualitative approach. Data collected through interviews and documentation. There were two penghulu opinions; Firstly, its use is permitted for reasons of convenience and technology use. This is in line with the maqashid sharia as an effort to maintain brides propoerty at the hajiyyah level. Second, its use must not be for the reason of avoiding marriage guardian identity and legal certainty in registering marriages. This is also in accordance with the maqashid sharia as an effort to maintain descendants at the tahsiniyyah level. In this condition, implementing taukil wali nikah through information technology is preferred over not implementing it.